Realizing Research Impact and the Experience of a Malaysian University - Ibrahim, Shaliza (Journal of Research Management and Governance, 2018)
This paper touches on a range of aspects that affect the realization of research impact. Malaysia has invested significantly in research and we have world class researchers who have proven themselves with high impact publications. However, there is still a lack of clear connection when it comes to relating research output to resources. This paper recommends proper initial research planning involving multi-sectorial stakeholders, and identification of impact and impact pathways in conceptualizing research projects. Strong institutional support in the form of professional research managers to assist researchers in research processes is important to ensure that the research activities are run smoothly and monitored well. . Initiatives to enhance researchers networking, mobility and competency through relevant training programmes will encourage our academics to expand their horizon and generate new ideas for research. Considering the amount of investment that has been made and the conducive environment that we have at universities, it may seem that we are not fully capturing or extracting all the results and products of our research endeavour. It is thus highly desired that Malaysia should have sound database and data management system to capture all the work that has been done and make the information accessible to research managers as well as researchers to do strategic analyses.